Loneliness subjective experience in the childhood of youngVenezuelan artists in situations of vulnerability and social exclusion - González-Aparicio, Ariadni (2026)
Young people from low-income neighborhoods in Caracas, Venezuela, experience vulnerabilityand social exclusion that derail their life trajectories. In this article, I focus on understandingthe subjective experience of loneliness in childhood among three young male artists (between 22and 24 years old) living in a context of vulnerability and social exclusion. Using a constructivistparadigm and a qualitative narrative design methodology, I collected their life stories andinterpreted them through Reflective Thematic Analysis. These young men experience profoundloneliness and helplessness in their early years, where play and creative activity serve as a wayto process the traumatic experiences they have endured.